Triplet chemotherapy with docetaxel, cisplatin and S-1 for unresectable advanced squamous cell carcinoma of the esophagus: phase I/II trial results - Ojima, Toshiyasu (Oncotarget, 2019)
BACKGROUND: Although triplet regimen of docetaxel, cisplatin, and 5-FU (DCF) reportedly yields high response rates for metastatic squamous cell carcinoma of the esophagus (SCCE), it has severe toxicity. In our previous phase II trial, grade 3/4 toxicities of neutropenia occurred in 68.8% of the patients. Development of chemotherapeutic regimen that does not impair quality of life of the patients with metastatic SCCE is therefore needed. A novel chemotherapeutic regimen combining docetaxel, cisplatin, and alternate-day administration of S-1 (modified DCS) may be associated with reduction of severe adverse effects. METHODS: This study is a single center phase I/II trial of chemotherapy using modified DCS regimen for patients with recurrent/unresectable SCCE. The phase I trial adopts a ‘3 + 3 patient cohort’, dose-escalating study design. In the phase II trial, the primary endpoint is evaluation of the overall response rate (ORR). Secondary endpoints are evaluation of drug-related toxicity, overall survival (OS), and progression-free survival (PFS). RESULTS: In the phase I trial, the recommended dose for docetaxel, cisplatin, and S-1 were 40 mg/m(2) (day 1), 50 mg/m(2) (day 1), and 80 mg/m(2)/day, respectively. In the phase II trial (n = 50), the ORR was 54 %. The median OS and PFS were 10 and 4 months, respectively. Grade 3/4 adverse events included neutropenia (26%), leukopenia (14%), anorexia (10%) and febrile neutropenia (6%). CONCLUSION: The modified DCS therapy for patients with advanced SCCE is feasible and safe in both chemotherapeutic and perioperative periods. Registration number: UMIN000016364.